Water use in Florida: Examining Perceptions of Water use Based on Visual Images - Joshua M. Epstein; Lisa K. Lundy; Alexa J. Lamm (Journal of Applied Communications, 2017)
Residents and decision makers often perceive information regarding water use differently. This is an issue in Florida where water quantity is a concern, and the distribution of accurate knowledge will be necessary to assist in effective conservation efforts. This study used two online surveys to gain insight into Florida residents’ and decision makers’ (county commissioners, county clerks and county managers) perceptions of water use based on visual images. Using non-probability opt-in sampling methods a total of 525 Florida residents’ responses were collected, and in a second survey 169 decision makers’ responses were collected. Respondents were asked to associate a specific water user, based on a visual, with high, moderate, or low water usage. A series of chi-square tests were used to compare and test for differences between Florida residents’ and decision makers’ perceptions, revealing that significant differences in perception did exist. The identification of these differences was used to develop recommendations for enhancing education and communication regarding water use.
Keywords: Framing; Social semiotics; Visuals; Water-use